Gross domestic savings: what influences it's growth in Kenya? - Julia Mwende Musyoka; Titus Mosoti Ogero (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
The study investigates the factors influencing gross domestic saving growth in Kenya during the period 1989 – 2018 using the McKinnon-Shaw Hypothesis. Ordinary least squares is employed to test for significance of individual parameters which may influence the level of gross domestic savings growth. The results indicate that gross domestic product growth rate, inflation rate and lending interest rate are significant in determining the growth in gross domestic saving. Capital formation was insignificant in influencing the growth in gross domestic saving. The results indicate the need for the government to enhance the prospects of economic growth which will lead to rise in domestic savings. The Central Bank of Kenya, as well, to set lending interest at a rate that encourages saving.